ICT usage in Malaysian SMEs: Analysis on ict adoption and perceived attributes - Said, Mazidah (2015)
The main objective of this study is to identify the level of ICT adoption among micro, small and medium categories of Malaysian SMEs from services sector. The empirical study from this research determined the relationship between perceived attributes of innovation elements and level of ICT adoption furthermore the ICT usage. From the probability proportionate stratified random sampling, 390 SMEs from the micro, small and medium categories as the respondents participated in the survey questionnaires. The data collection was performed throughout Malaysia by email, telephone calls and exhibition. The results were analyzed by descriptive statistic, correlation, multiple regression and ANOVA analysis. This empirical study revealed that 75.1% SMEs in service sectors at Level 3 – Advanced Communication, followed by 12.3% at Level 4 – Advanced Information Technology, 6.4% at Level 2 – Basic Information Technology and 6.2% at Level 1 – Basic Communication. The profile of ICT usage measured by the list of core ICT indicators was developed from the primary data gathering. Previous research has indicated that the rate of adoption of ICT innovation specifically among SMEs in Malaysia was low although there are many initiatives have been implemented by the government but the outcomes have not been fully translated into results. This is important to improve the performances by adopting the ICT innovation as SMEs are key drivers and engine for the economic growth. More importantly, ICT are among the National Key Economic Areas (NKEAs) that need to be focus especially for the purpose of SMEs development. Perceived attributes of innovation are important elements that have been considered in this study since it contributed up to 87% to the rate of adoption and core ICT indicators as the guidance adhered to globally accepted standards. Thus, the information on the current status is important before further develop the action plan. This study provided the useful information as the guidance to policy maker by created the identification of level ICT adoption and relate with the profile of ICT usage based on the list of core ICT indicators as the standard measuring tools. The practical implications to policy maker as well as society are to suggest the ICT trialability package, human capital development programs to increase the ICT-skilled workforce and empowering bottom 40 percent micro SMEs through ICT utilization along the business value chain. Mainly, the findings supported government agenda towards developing the SMEs as stated in SME Masterplan (2012-2020), Third Industrial Master Plan (IMP3), Tenth Malaysia Plan (10MP) and contribute to the government aspirations to become high income and developed nation by 2020 as stated in New Economic Model (NEM).